Neurocognitive deficits and sequelae following severe hand, foot, and mouth disease from 2009 to 2017, in JiangSu Province, China: a long-term follow-up study. (February 2022) - Ji, Hong; Fan, Huan; Ai, Jing; Shi, Chao; Bi, Jun; Chen, Yin-Hua; Lu, Xiao-Peng; Chen, Qin-Hui; Tian, Jian-Mei; Bao, Chang-jun; Zhang, Xue-feng; Jin, Yu
Highlights: HFMD cases with more severe CNS complications are linked to neurological sequelae. Cognitive dysfunction is aggravated in HFMD cases with more severe CNS complications. The risks of sequelae and cognitive deficits are similar among different pathogens. HFMD cases without/with mild CNS involvement did not present with any sequelae. Cognitive function was also associated with socioeconomic factors. Abstract: Background: The aim of this study was to evaluate the long-term sequelae and cognitive profiles resulting from severe hand, foot, and mouth disease (HFMD) with central nervous system (CNS) involvement. Methods: 294 HFMD cases were included in a retrospective follow-up study. Physical examinations were conducted. The Chinese Wechsler Preschool and Primary Scale of Intelligence, Fourth Edition (WPPSI-IV) was used to assess intelligence. Results: 58 mild HFMD cases and 99 severe HFMD cases with mild CNS involvement did not present any neurological sequelae. In comparison, the sequelae incidence for severe HFMD with more severe CNS complications was 50.0%. The proportion of full-scale intelligence quotient (FSIQ) impairment was 45.0%. In the 2:6–3:11 age group, severe HFMD with more severe CNS complications and lower maternal education level were risk factors for verbal comprehension disorder. Urban–rural residence and lower paternal education level were risk factors for FSIQ disorder. Furthermore, in the 4:0–6:11 age group, severe HFMD with more severe CNS complication was a risk factor for visual spatial disorder and fluid reasoning disorder. Lower paternal education level was a risk factor for FSIQ disorder. Conclusion: Early assessment and intervention among severe HFMD patients with more severe CNS involvement at a very young age will prove beneficial for their future performance.